Mechanisms of Hypercoagulability - Dahl, Ola E. (Thrombosis and Haemostasis, 1999)
Patients undergoing major traumas, major joint replacement surgery, and neurosurgery are at high risk for postoperative deep vein thrombosis (DVT). Even if modern low molecular weight heparin is given as prophylaxis, the frequency of DVT remains high in these patients.1-7 This may indicate that some patients possess a certain “heparin resistance,” due probably due to an overwhelming procoagulant activity and/or because the hypercoagulable state lasts for a longer time than presently assumed. Tissue factor (TF) is the primary cellular initiator of blood coagulation and the most potent trigger of blood clotting known today.8 Adventitia surrounding the major blood vessels, the brain, and the bone marrow are structures with high levels of TF.9 Elective hip replacement surgery, which is a fairly well-standardized procedure that involves a great deal of damage to the bone marrow, is therefore, well-suited as a model to study the mechanisms of hypercoagulability.